Substituição do aço inoxidável em uma coluna de destilação por material polimérico de menor custo - Cunha, Caroline Barlette da (2017)
The ethanol production in small scale, with maximum capacity of 5.000 l/day, deals with serious problems related to low process performance, due to the low extraction of raw material, inefficiency of ethanol separation present in the fermented and also the high energetic consumption. Other points to highlight involving this activity, are the high economic costs associated to the work force, especially the distillation process and the high investment for the distillation columns fabrication. Due to the reasons above, the present work aims to propose a new concept of low cost distillation columns by the replacement of stainless steel with a polymeric material. This idea intends to promote the decrease of equipment costs and assist in the production of ethanol in small scale. The experimental part consisted initially of choosing nine polymeric materials, based on costs, namely: polyamide 6,0 (PA 6,0), polypropylene (PP), high density polyethylene (HDPE), polyvinyl chloride (PVC), polycarbonate (PC), poly methyl methacrylate (PMMA), bakelite, polyurethane (PU) and the composite of unsaturated polyester resin reinforced with 30% glass fiber (GFRP). Then, they were submitted to chemical resistance tests in contact with ethanol, according to the standard ASTM D543, at temperatures of 90°C and 115°C. By determining the degree of swelling and the area increase in, it was found that the amorphous samples presented the worst performance, whereas the semicrystalline samples of PP and HDPE together with the GFRP composite presented the best answers. Thus, the materials with best performance in the initial selection (PP, HDPE e GFRP), were submitted to new chemical resistance tests, in contact with ethanol in different concentrations, being 85% e 96%, and at different temperatures, of 90 and 115°C. The tested samples with ethanol in 85% were characterized by DRX, FTIR and mechanically tested by three-point flexural tests. Whereas the samples tested with 96% ethanol were analyzed by the techniques already mentioned and also by DSC. The results obtained for the materials at both concentrations were satisfactory, demonstrating a good response of PP and HDPE polymers, due to its behavior that presented a small diffusion of the ethanol. Moreover, they presented very satisfactory results in the mechanical tests. On the other hand, the GFRP presented a loss of mass after the chemical resistance tests, as well as being inefficient as a constructive material of distillation columns, due to the very expressive drop of their maximum flexion tension after the contact with ethanol, in both concentrations. Furthermore, the economic attractiveness of the idea proposed in this work was evaluated, and the results obtained showed a very positive reduction of costs involved in the construction of a polymer distillation column.